Bardas Blancas: transhumance, agency and memory. Biography of a rural territory (Huellas, 2025)
This article reconstructs the territorial history of the Bardas Blancas area, located in the department of Malargüe, in the south of the province of Mendoza (Argentina), from an ethnographic and historical-geographical approach. Through fieldwork and comparative analysis of oral sources, local records and historical documents, it investigates how peasant and indigenous families have shaped a transhumant territoriality that challenges official narratives about rural marginality. The reconstruction of the space occupation and socialization process allows for an analysis of the persistence of pastoral livestock practices in a context marked by environmental aridity, extractive expansion and limited state presence. From a critical geography perspective, it is argued that territory is not merely a physical support but a social and symbolic construction in which memory, identity and material reproduction converge. Bardas Blancas is thus presented as an example of vivid and resisted geography, where the meanings of place are contested between the promises of energy development and the rationalities of peasant subsistence. The work contributes to debates on rurality and territorialization, highlighting local forms of agency and rootedness that persist on the margins of state and productivism discourses.